Attitudes of teachers towards information technology in education in Miri - Ting, Kai Chu (1998)
The purpose of this study is to investigate how teachers will respond and react to the impending introduction of information technology to schools. Specifically, it aims to uncover their attitudes towards the educational use of this technology. Another important aspect of the study is to identify factors which affect their attitudes. A positive attitude on the part of teachers is crucial if any change is to be successfully accomplished.